No evidence for reduced growth in resident fish species in the era of de-eutrophication in a coastal area in NW Europe. (July 2021) - Bolle, Loes J.; Hoek, Ruben; Pennock, Ineke; Poiesz, Suzanne S.H.; van Beusekom, Justus E.E.; van der Veer, Henk W.; Witte, Johannes IJ.; Tulp, Ingrid
Abstract: Coastal areas in north-western Europe have been influenced by elevated nutrient levels starting in the 1960s. Due to efficient measures, both nitrate and phosphate levels decreased since the mid-1980s. The co-occurring declines in nutrient loadings and fish productivity are often presumed to be causally linked. We investigated whether four resident fish species (twaite shad, bull-rout, thick-lipped grey mullet and eelpout), that spend the majority of their life in the vicinity of the coast, differed in growth between the historic eutrophication period compared to the recent lower nutrient-level period. Based on Von Bertalanffy growth models of length at age, and the analysis of annual otolith increments, we investigated the difference in sex-specific growth patterns and related these to temperature, eutrophication level (Chlorophyll a ), growth window and fish density. In all four species, annual otolith growth rates during the early life stages differed between the two periods, mostly resulting in larger lengths at age in the recent period. All species showed significant correlations between increment size and temperature, explaining the observed period differences. The lack of an effect of total fish biomass provided no evidence for density dependent growth. A correlation with chlorophyll was found in bull-rout, but the relationship was negative, thus not supporting the idea of growth enhanced by high nutrient levels. In conclusion, we found no evidence for reduced growth related to de-eutrophication. Our results indicate that temperature rise due to climate change had a greater impact on growth than reduced food availability due to de-eutrophication. We discuss potential consequences of growth changes for length-based indicators used in management. Graphical abstract: Image 1 Highlights: Growth study based on an unique otolith collection in terms of species and timespan. No evidence that de-eutrophication is detrimental for fish growth. Temperature rise is the main driver of changes in growth.